ROOT RESORPTION OF PERMANENT INCISORS DURING THREE MONTHS OF ACTIVE ORTHODONTIC TREATMENT - Batool, Iffat; Abbas, Hasnain; Abbas, Assad; Abbas, Iram (Journal of Ayub Medical College Abbottabad, 2010)
Background: Root resorption is one of the most common and undesirable sequelea of orthodontic treatment. The aim of this study was to evaluate the amount of root resorption in permanent incisors during 3 month active period of fixed orthodontic appliance therapy using periapical radiographs. Methods: Periapical radiographs of a total of 138 permanent teeth (n=138, mandibular n1=52, maxillary n2=86) were evaluated for root resorption. All patients were treated with 3M MBT multibonded, pre-adjusted appliances with 0.022 inch slots. Initial levelling and alignment was achieved with 0.0175 inch co-axial wires. All four incisors (maxillary and mandibular) were measured for any change in root length. The change in root length between T0 (pre-treatment) and T1 (post-treatment) was measured in millimetres and expressed in terms of percentage of original root length. Results: The mean pre treatment (T0) root length for the maxillary teeth (n1=62) was 19.27±2.86 mm and 20.01±2.57 mm for the mandibular teeth (n2=31). The post-treatment (T1) root length for the maxillary teeth was 18.96±2.85 mm and 19.49±2.4 mm for the mandibular teeth showing a mean resorption of 0.31 mm and 0.52 mm for the maxillary and mandibular teeth respectively. Conclusion: Root resorption was strongly correlated with active orthodontic appliance therapy with maxillary and mandibular incisors being most susceptible. It was found that root resorption can be detected even in the early levelling and alignment stages of orthodontic treatment. Keywords: Root resorption, incisor, orthodontics, dental radiography